Evaluación de la aplicación de dos bioinsumos: Bacillus subtilis y Trichoderma spp en precosecha y poscosecha de tomate riñón (Lycopersicum esculentum) Campus Salache, Latacunga, Cotopaxi 2022. - Sánchez Quinatoa, Carlos Fabricio (2022)
This research project was carried out in the province of Cotopaxi Parroquia Eloy Alfaro Salache campus in the laboratory of the Agronomic Engineering career. Its objective was to evaluate the application of two bioinputs bacillus subtilis and trichoderma spp in pre-harvest and post-harvest kidney tomato (Lycopersicum esculentum) Campus Salache, Latacunga, Cotopaxi 2022”. A complete randomized block design with a factorial arrangement of 2 x was applied. 2 x 3 x2, giving a total of 24 treatments and 72 experimental units. Its description is as follows: two seasons, two bio-inputs, three doses and two color indices. The doses of bioinputs applied were 0.0g, 5.0g and 7.5g applied in pre-harvest and post-harvest. The indicators evaluated were incidence of physiopathies, weight loss, firmness, pH, total solids and ashes. The following results were obtained: Within the application seasons, the best season was E2 (postharvest) with 6.67% of physiopathies; 2.06 kg of firmness, 4.17 °Brix and 20.36% ash, while E1 (pre-harvest) presented 9.11% weight with respect to pH and humidity did not show significance. Regarding the bioinput, the best was B2 (Trichoderma spp) with averages of 7.78% of physiopathies; 2.06 kg of firmness, 4.19 °Brix and 20.87% ash, while B1 (Bacillus subtilis) presented 9.06% weight loss and 4.37 pH. The doses that show the best results are D3 (7.5 g) with 5% physiopathies, while 2.06 kg firmness and 20.09% ash, in terms of weight, pH, soluble solids and non-humidity. showed significant values. The best color for harvest was C1 (10% red) with averages of 7.91% weight loss; 2.06 kg of firmness, 4.36 pH, while color C2 (10 to 30% red) presented 4.18 °Brix, in which it refers to physiopathies, humidity and ashes, none of the indexes of harvest showed significance.